2012
DOI: 10.1016/j.jpag.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Recent Vaginal Douching among African American Adolescent Females

Abstract: Study objective To describe the prevalence and correlates of vaginal douching among urban African American adolescents and to examine the association between douching and STI status. Design: Demographic, psychosocial, and behavioral data were collected through cross-sectional, self-administered surveys. Self-collected vaginal swabs were assayed using NAAT for trichomoniasis, Chlamydia, and gonorrhea. Setting Sexual health clinic in a large metropolitan area of the Southeast Participants African American fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
3
14
0
1
Order By: Relevance
“…Douching was observed more among women with no formal education or among those with only primary education. This agrees with other studies that douching is more prevalent among females of low educational [15,39] and socioeconomic status [7]. However, our result of douching being more prominent in younger age groups was in contrast with what Declemente et al reported [7].…”
Section: Disclosuresupporting
confidence: 87%
See 1 more Smart Citation
“…Douching was observed more among women with no formal education or among those with only primary education. This agrees with other studies that douching is more prevalent among females of low educational [15,39] and socioeconomic status [7]. However, our result of douching being more prominent in younger age groups was in contrast with what Declemente et al reported [7].…”
Section: Disclosuresupporting
confidence: 87%
“…Sources of BVF which collect in the vagina are from the peritoneal fluid, fluid from the entire uterine system which includes the follicles, the fallopian tubes, the uterus itself, the cervix and the vaginal The epidemiology of douching, women's behavioral pattern to it, substances used and reasons behind douching as well as its health implication have been studied extensively, mostly outside of Africa [2,3]. Surveys have shown that douching practice was common in the United States [4,5] Martino, et al stated that [6] douching prevalence varies according to race, and age cohort and Diclemente argued that increased age [7], lower socioeconomic status, and older partners are probable relevant risk factors for douching among African American adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have observed a significant correlation between factors that depict individual socio-economic status and health awareness and practices. Socio-economic status may influence health by limiting access to preventative and treatment services and shaping health behaviors (Santelli et al, 2000;Simms and Stephenson, 2000;Diclemente et al, 2012). Hence, socio-economically disadvantaged populations are likely to be strongly affected by various health problems and adopt practices such as VD that may result in increased risks of gynecological problems.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, socio-economically disadvantaged populations are likely to be strongly affected by various health problems and adopt practices such as VD that may result in increased risks of gynecological problems. In addition, worse health indicators (such as high prevalence of VD) are common in such populations, suggesting that women in low socio-economic classes douche more often than those in high socioeconomic classes (Cotrell, 2005;Diclemente et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, IVPs are used for cleansing, and intravaginal insertion is used to create a warm and tight vaginal environment to please male partners, a partner preference associated with traditional and cultural expectations of women 1517. Among HIV-uninfected women in the US, douching is common and primarily motivated by vaginal hygiene 18,19. Few studies have addressed IVP among HIV-infected women, in whom IVP may be implicated in the development of BV, obstetric and gynecological complications, and HIV transmission 2,611…”
Section: Introductionmentioning
confidence: 99%